The gut microbiota and endometriosis: From pathogenesis to diagnosis and treatment - Qin, Rui; Tian, Gengren; Liu, Junbao; Cao, Lu (Frontiers in Cellular and Infection Microbiology, 2022)
Endometriosis is a common gynecological disease, which often leads to pain and infertility. At present, the specific pathogenesis of endometriosis has not been clarified, which may be closely related to the imbalance of sex hormones in the body, ectopic hyperplasia stimulated by immune inflammation, and invasion and escape based on tumor characteristics. Gut microbiota is associated with many inflammatory diseases. With the further study of gut microbiota, people pay more and more attention to its relationship with endometriosis. Studies have shown that there is an association between gut microbiota and endometriosis. The specific ways and mechanisms of gut microbiota participating in endometriosis may involve estrogen, immune inflammation, tumor characteristics, etc. Therefore, in the future, regulating gut microbiota disorder in various ways can help the treatment of endometriosis patients. This study reviewed the research on gut microbiota and endometriosis in order to provide ideas for clinical diagnosis and treatment.